2017
DOI: 10.4103/2348-0548.197435
|View full text |Cite
|
Sign up to set email alerts
|

‘ROSE concept’ of fluid management: Relevance in neuroanaesthesia and neurocritical care

Abstract: Fluid therapy in neurosurgical patients aims to restore intravascular volume, optimise haemodynamic parameters and maintain tissue perfusion, integrity and function. The goal is to minimise the risk of inadequate cerebral perfusion pressure and to maintain good neurosurgical conditions. However, fluid management in brain-injured patients has several distinctive features compared with non-brain-injured critically ill patients. The ROSE concept advocates the restriction of fluids, which is consistent with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The goal is to maintain tissue perfusion, integrity, and function while restoring intravascular volume to maximize hemodynamic parameters. (12). It is matched with Malbrain's statement that also recommend the ROSE concept of fluid balance therapy, which shows the relationship between positive fluid balance and overload fluid in critically ill patients (13).…”
Section: Discussionmentioning
confidence: 77%
“…The goal is to maintain tissue perfusion, integrity, and function while restoring intravascular volume to maximize hemodynamic parameters. (12). It is matched with Malbrain's statement that also recommend the ROSE concept of fluid balance therapy, which shows the relationship between positive fluid balance and overload fluid in critically ill patients (13).…”
Section: Discussionmentioning
confidence: 77%
“…Albumin can be used as a volume expander and an alternative to avoid unnecessary fluid administration in cardiac surgery. [7][8][9][10][11][12] Cost efficiency is the main reason why protein colloids such as albumin 4-5% are not used as first-line fluid therapy. The effectivity in giving protein colloid post-cardiac surgery is well-established, although it is still not given in the first-line fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The World Federation of Societies of Intensive and Critical Care Medicine Task Force suggested that healthcare practitioners should prioritize giving patients and families a voice in decision-making and patient-centered care.This method involves managing mental health disorders in critically ill individuals with the right use of medications. Fluid management is a concept that Monteiro and Goraksha (2017) presented, and it is relevant to neurocritical care for patients with mental health issues. The idea emphasized the significance of individualized fluid management, taking into account elements including hemodynamics, brain edema, and electrolyte imbalances.…”
Section: Literature Reviewmentioning
confidence: 99%